Evaluation of C3435T MDR1 Gene Polymorphism in Adult Patient with Acute Lymphoblastic Leukemia - Miladpoor, Behnoosh; Tavassoli, Alireza; Meshkibaf, Mohammad Hassan; Kha, Fateme (Journal of Medicine, 2011)
Background: P-glycoprotein (P-gp) is a transmembrane pump encoded by MDR1 gene. It contributes in protection of the cells against xenobiotic and toxic compounds. P-gp also contributes in multidrug resistance in acute lymphoblastic leukemia (ALL). Human MDR1 polymorphism include C to T exchange at position 3435, individuals with TT polymorphism have lower expression of P-gp than the others with CC genotypes. Accumulation of xenobiotics in the cells can cause some diseases like cancers. Materials and Methods: To evaluate MDR1C3435T gene polymorphism in adult patients with ALL, 54 patients and 96 healthy controls were involved in our survey. Genotyping of ALL patients and healthy controls was performed by Polymerase Chain Reaction – Restriction Fragment- Length Polymorphism (PCR-RFLP). Data analysis was done by SPSS software through T-test and Chi- Square. Results: No significant difference was found between C3435T MDR1 gene polymorphisms and incidence of ALL in adult patients. Also there was not any significant difference between T and C alleles and incidence of ALL. Conclusion: C3435T MDR1 polymorphism is not associated with the incidence of ALL in the population studied. Keyword: P-gp; C3435T; MDR1; ALL; polymorphism DOI: 10.3329/jom.v12i1.5541 J Medicine 2011; 12 : 3-6